High-Purity Preparation of Enzyme Transformed Trans-Crocetin Reclaimed from Gardenia Fruit Waste - Charng-Cherng Chyau; Chu-Ying Chiu; Hung-Lin Hsieh; David Wang-Chi Hsieh; Chong-Ru Hsieh; Chi-Huang Chang; Robert Y. Peng (Plants, 2022)
The recovery of physiologically bioactive ingredients from agricultural wastes as an abundant and low-cost source for the production of high value-added mutraceuticlas has been recognized and supported for the commercial interests and sustainable managements. In the extraction of geniposide for the development of natural food colorants from the dried fruits of Gardenia jasminoides Rubiaceae, the gardenia fruit waste (GFW) still remaining 0.86% (w/w) of crocins has always been discarded without any further treatments Until now, there was no simple and effective protocol for high-purity trans-crocein (TC) preparation without the coexistence of non-biologically active cis-crocein from GFW. We proposed an effective process to obtain the compound as follows. Crocins were extracted firstly by 50% of ethanol in the highest yield of 8.61 mg/g (w/w) from GFW. After the HPD-100 column fractionation in the collecting of crocins, the conversion ratio of 75% of crocins to crocetins can be obtained from the commercial available enzyme- Celluclast® 1.5 L. The crocins hydrolyzed products, were then separated through the HPD-100 resin adsorption and finally purified with the centrifugal partition chromatography (CPC) in single-step to obtain TC in a purity of 96.76 ± 0.17%. Conclusively, the effective enzyme transformation and purification co-operated with CPC technologies on crocins resulted in a high purity product of TC may be highly application in the commercial production.